Service Quality and Student Referral Intentions in Higher Education: The Mediating Role of Student Satisfaction at Islam Syekh-Yusuf University - Salsa Damanik; Sugeng Lubar Prastowo; Yosi Safri Yetmi (PT. Batari Edu Calya, 2026)
This study examines how five dimensions of service quality—tangibles, reliability, responsiveness, assurance, and empathy—shape student referral intentions through student satisfaction at Islam Syekh-Yusuf University, Indonesia. A sequential exploratory-to-confirmatory design was used: preliminary interviews contextualized service issues and informed the survey, followed by a cross-sectional questionnaire administered to 175 students from the 2021–2022 cohorts selected using proportional random sampling. The structural model was estimated with partial least squares structural equation modeling (PLS-SEM) in SmartPLS 3.2.9. The results show that assurance is the only SERVQUAL dimension with a statistically significant positive effect on student satisfaction (β = .386, p = .003). Student satisfaction, in turn, strongly predicts referral intention (β = .583, p < .001). Assurance also has a significant indirect effect on referral intention through satisfaction (β = .225, p = .005), whereas the other indirect effects are not significant. The model explains 51.7% of the variance in student satisfaction and 72.9% of the variance in referral intention. Internal consistency and convergent validity are acceptable; however, several heterotrait–monotrait (HTMT) ratios exceed the conventional .90 threshold, indicating that discriminant validity is not fully established for some construct pairs. The study therefore supports a focused managerial implication: competence, credibility, security, and clear communication are central to satisfaction-driven student referrals, while the non-significant dimensions should not be interpreted as unimportant without addressing measurement overlap and contextual heterogeneity.